Plasma hormone levels in the green turtle Chelonia mydas reared under captivity as a tool to predict mating and oviposition - Rubin, Olga; Soffer, Osher; Levy, Yaniv; Aizen, Joseph (Frontiers in Marine Science, 2023)
Circulating estradiol (E2), testosterone (T) and progesterone (P4) concentrations, and blood chemistry were monitored in the female green turtle Chelonia mydas over continuous seasons at the Israel sea turtle breeding facility. The tested factors were analyzed with regard to the female`s nesting activity in the subsequent nesting season: Future nesters (FN) and Non-nesters (NN). Our analysis showed significant changes in all three sex steroids, E2, T, P4, and in 13 blood biochemical parameters between the two females` groups. All females presented consistent E2 profiles from year to year, with a single elevation in September in FN females. P4 concentrations in nesting females were high in April (mating) and higher towards the beginning of June due to oviposition, females that presented concentrations above 1ng/ml had successful oviposition (8 females: 1 female in 2018, 5 in 2019 and 2 in 2020). T profiles were high at the onset of vitellogenesis towards November and again high during April. We were able to predict which females would undergo oviposition with a specific profile seen only in FN females - elevated P4 concentrations from February to June and the elevation of metabolites electrolytes and Gamma-Glutamyl Transferase (GGT) concentrations toward November. This will facilitate selectively choice mating pairs to ensure that the Mediterranean population genetic variability is maintained. Clutches per female were between 2 and 6, with 25 in total. Females laid an average of 91 ± 7 eggs (range 39-139 eggs) per nest with emergence rate of ~10% (0-58%). Overall, the same trend in circulating steroid concentrations was revealed over the years in the females reaching oviposition only when a certain threshold was achieved. In this study all the factors mentioned above can indicate an upcoming oviposition at least 6 months prior to nesting as seen in the PCA analysis. This information can contribute to the success of green sea turtle breeding programs in captivity and will hopefully help the Israeli Rescue Center predict and prepare for nesting activities in the years ahead.